Stakeholders' perceptions of 10 years of the Global Action Plan for Influenza Vaccines (GAP) – Results from a survey. Issue 45 (26th October 2016) - Nannei, Claudia; Goldin, Shoshanna; Torelli, Guido; Fatima, Hiba; Kumar, Kaveri; Bubb-Humfryes, Oliver; Stenson, Bo; Sparrow, Erin
Abstract: Ten years after the launch of the Global Action Plan for Influenza Vaccines (GAP), the World Health Organization (WHO) surveyed stakeholders to understand their perceptions of what the programme had achieved. This article provides a summary of the findings; the full report will be available on-line on the GAP website in November 2016 (http://www.who.int/influenza_vaccines_plan/en/ ). Seventy-seven responses were received from stakeholders including medical doctors, national influenza center officials, country immunization programme teams, surveillance and disease centers, policy-makers, researchers, vaccine manufacturers, and non-governmental organizations from 28 countries, representing all six WHO regions. Respondents cited GAP's biggest successes as capacity building in developing countries; raising international awareness of global needs in the event of a pandemic; and collaborative alignment of influenza stakeholders. The most commonly reported challenges were the limited progress in development of a broadly protective or universal vaccine and the perceived absence of a major increase in seasonal demand. These findings aligned with the perception that less global progress had been made under the third GAP objective, focused on research and development of better vaccines, than on increasing seasonal vaccine use (objective 1) and pandemic vaccine production capacity (objective 2). Respondents explained what they saw as the major challenges to development of better vaccines, including to development of a universal influenza vaccine. The majority of respondents agreed that the goal chosen at the GAP II consultation is still relevant. Results highlighted the importance of promoting research and development of better vaccines, both for facilitating uptake of seasonal vaccines and for ensuring timely vaccine availability in the event of a pandemic. As the GAP concludes its mandate this year, these findings will contribute to discussions on the impact of programme closure and how to address the key issues facing influenza stakeholders thereafter.